Preparation and properties of renewable polyesters based on lignin-derived bisphenol. (26th October 2021) - Hanson, Kalin G.; Lin, Ching-Hsuan; Abu-Omar, Mahdi M.
Abstract: The biophenol molecule isoeugenol has been shown to be a major product of lignin-first reductive catalytic fractionation (RCF) of lignocellulosic biomass. The use of isoeugenol as a starting material for biobased polyesters is described here. A series of novel biobased polyesters have been synthesized from lignin-derived bisphenol and various acyl chlorides via a polycondensation reaction. NMR spectroscopy was used to confirm the structure as well as to approximate molecular weight. Thermal properties of the resulting biopolyesters are directly related to the length of the aliphatic chain of the diacid. Glass transition temperatures were in the range from 19 °C to 108 °C and can be tuned to be more in line with that of petroleum-based polyesters such as PET (Tg = 80 °C) by employing mixtures of lignin-based bisphenols (Tg = 83 °C). In addition to thermal tunability, these renewable polyesters can have up to 100% bio-content by mass. Graphical abstract: Image 1 Highlights: Lignocellulosic biomass is a viable feedstock for aromatic monomers Isoeugenol can be used as a starting material for biopolyesters Thermal properties of biopolyesters can be tuned to desired properties Biopolyester properties are directly related to aliphatic chain length